Structural and Functional Features of the Thymus Under Some Impacts (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the study of the protective and compensatory mechanisms of the thymus, that is, the study of its adaptive reactions to antigenic and non-antigenic effects. These changes are based on the structural and functional response to stress.